KAJIAN KARAKTERISTIK PEMBUATAN EDIBLE FILM DENGAN KOMBINASI PATI BIJI NANGKA DAN ALGINAT SEBAGAI PENGEMAS MAKANAN BERBASIS BIODEGRADABLE (Study Characteristic Of Making Edible Film With Combination Of Jackfruit Starch And Alginat As Biodegrdable Food Packaging) - Azafilmi - Hakiim; Dessy Agustina Sari (Universitas Muhammadiyah Semarang, 2017)
The aim of this research is to get the optimum starch and alginate seed starch composition and the most suitable operating temperature during the manufacture and printing of edible film. The experimental design was variation in starch seed starch concentration (1.5%, 2.5%, 3.5%), alginate consentation (0.5%, 1%, 1.5%), and operating temperature (750C, 900C). The result of the research on the parameter of modulus young value or the highest average film elasticity level is 314,08 Mpa obtained at 2.5% alginate composition, 1.5% jackfruit seed starch and operating temperature 90oC, extention at maximum or highest film elongation value average of 31.59 mm in 3.5% alginate composition, 1.5% jackfruit starch and 90oC operating temperature, tensile strength value or tensile strength value of an average film average of 7.45 Mpa obtained in composition 3 , 5% alginate, 1.5% jackfruit starch and 90oC operating temperature. By using SPSS series 23 there is a correlation of linear regression response extention at maximum and tensile strength is increasing. Key words : starch, alginat, edibel film.